A selection methodology for faster acceptance of the estimation of loss distribution models. - Luo, Xiao Rong. (2008)
Losses will be made whenever insured accidents occur, and the total claims are the sum of a random number of random claim amounts. This research project will concentrate on one of the components of the total claim amount- the individual calim amount, assuming that the individual calim amounts are drawn from a particular distribution, called a loss distribution.